Sífilis congênita: levantamento no berçário do Hospital Universitário Antônio Pedro da Universidade Federal Fluminense - Período: 1990/1992 - Freitas, Fátima Pires de; Vasconcellos, Jacqueline; Coutinho, Kátia Nazaré Tabosa; Mattos, Marize Lopes Veríssimo de; Dutra, Ronie de Oliveira; Gouvêa, Tegnus Vinicius Depes de; Gomes, Marco Antonio (Brazilian Journal of Sexually Transmitted Diseases, 1994)
The presence ofthe syphilis in firtile women can precipitate the increase of congenital syphilis. A preventive solution consist of precocious diagnosis and treatment of i nfected pregnants. A clinicai actualization is presented, relative to the epidemiology, detection and treatment of congenital and maternal syphilis. The most important risk factor is the lack of antenatal control, that must be initiated in the first month ofpregnancy, and the exams for infection detection made more than one time. ln this work we analysis the behaviour of congenital syphilis among living new-borns with the VDRL reactor in the period of 1990- 1992, in the HUAP-UFF, based on some variables, select in patients' cards of its maternity hospital. In our sample, we notice a gradual decrease of this pathology.